Evaluation of Domestic Apprenticeship Programs as an Effort to Improve Competency of Job Seekers in Lampung Province - Asmiati, Asmiati; Sulistiowati, Rahayu; Prihantika, Ita (Utan Kayu Publishing, 2023)
The domestic apprenticeship program in Lampung Province still encounters problems, such as the socialization process that is carried out less than optimally so that only a few companies are interested in collaborating. As a result, the company's recruitment implementation has not been able to achieve the specified target. This study aims to evaluate the implementation of the domestic apprenticeship program and identify the factors supporting and inhibiting the implementation of the domestic apprenticeship program in Lampung Province. The study was conducted with a qualitative descriptive approach using 4 program evaluation indicators consisting of input evaluation, process evaluation, outcome evaluation, impact evaluation (Wirawam, 2016). The results of this study indicate that the overall achievement of this domestic apprenticeship program is quite good so that this program can be continued by modifying or improving some that are less effective in order to achieve maximum results/targets for the coming year. Supporting factors in this domestic apprenticeship program are supported by complete facilities and infrastructure to support program implementation and are supported by competent instructors in training and guiding participants and inhibiting factors: lack of human resources, lack of commitment, domestic apprenticeship programs have not gone hand in hand with independent campus internship program and insufficient incentives.